Determinants of factors affecting the financial performance of Indian general insurance firm: Panel data evidence - Soumya Sasidharan; V. K. Ranjith; Sunitha Prabhuram (Contemporary Economics, 2023)
The researchers aim to examine the firm-specific variables that impact the financial performance of general insurance firms in India. The study's scope is limited to India's insurance industries from 2010-2011 to 2019-2020. The research considers 21 insurance firms in India out of 35 general insurers. We obtain statistical data from the financial statements of insurance companies. The research used correlation analysis and panel data regression to evaluate financial performance and its impacts. Panel data techniques were employed in the analysis to study the impact of eleven micro factors on the monetary performance of general insurers in India. The influence of micro (internal) variables such as capital adequacy ratio, firm size, age of the firm, retention, liquidity, loss ratio, investment ratio, reinsurance dependence, financial leverage, tangibility, and premium growth rate on the financial performance has been determined using econometric findings in this research. The fixed-effect model results reveal that firm's age, loss ratio, size, premium growth, and retention ratio are vital in affecting the financial performance of Indian general insurance firms. On the other hand, liquidity and financial leverage are insignificant in determining the financial performance of general insurance firms in India.
Keywords: C19; F61; G22; G32; 330; financial performance; financial leverage; general insurance; premium growth; panel data regression